AN IMPACT OF EQUIPMENT SELECTION ON CONSTRUCTION PROJECTS: CASE STUDY OF A ROAD PROJECT IN EGYPT - Osman, Elbadr; A. Mohy, Amr (Journal of Applied Engineering Science, 2022)
The use of equipment in the construction industry has expanded in recent years due to the equipment’s ability to complete most work items such as excavation work, casting, and more in a relatively short period of time. However, the real challenge would be selecting the appropriate equipment and accurately predicting the productivity of the equipment. In most projects, the choice of equipment to execute any work is based mainly on the expertise of contractors without taking into account any aspect of equipment’s life. Therefore, any insufficient construction equipment planning and management would have a huge undesirable effect on the time and cost of any project. The main aim of this research is to study the impact of equipment selection on the productivity of construction excavation sites and its effect on time and cost through a road project in Egypt as a case study. A highway road excavation project in Egypt with a total length of 7.2 km (4.5 miles). The impact would be determined by monitoring the progress of earthmoving activities and conducting a comparison between the estimated and actual productivity of equipment (long boom backhoe). The progress data was collected over 30 days for eight working hours per day for each piece of equipment. As a result of the poor equipment management, the actual productivity was 50% of the predicted rate, and that impacted the project’s cost by a 71.5% increase and by a 72% increase in the duration.